Regulation in Swiss Cantons: Data for one Century - Simon Luechinger; Mark Schelker (Center for Economic Studies and ifo Institute (CESifo), 2015)
In this paper, we present and illustrate novel data on more than a century of regulation in Switzerland. We provide quantitative measures for Swiss cantons on the annual stock of legally binding rules from 2006-2013 and on regulatory activity as reflected in the annual changes to such regulation from 1908-2013. We measure the stock of regulation by the number of enactments and characters, and the regulatory activity by the number of changed enactments and pages. Further, we break down the measures by the level in the hierarchy of legal norms and by the issuing authority. The data reveal substantial cantonal heterogeneity in the stock of regulation and the amount and development of regulatory activity. Regulatory activity generally increased over the century, though in a non-monotonic manner, and is characterized by substantial volatility. Quantitatively, the most important is regulation at the level of decrees. When focusing on the issuing authority, it is the executive that dominates. We also construct our measures for the federal level from 2006-2013 (stock) and 1848-2013 (activity).
Keywords: H10; H70; K20; Y10; 330; regulation; regulatory activity